Elementy kalkulacji kosztów i marż w wyznaczaniu rynkowej wartości cen transferowych - Zimniewicz, Natalia (Elements of Cost and Margin Calculation in Setting the Market Value of Transfer Prices, 2006)
Setting the level of transfer prices according to the arm's length principle proceeds according to a specific methodology. The very important aspects of this calculation are costs and margins used in transfers between related parties. Their level is determined by the tools of management accounting and financial analysis peculiar to rules defined in national and international tax regulations. In many aspects these rules are different from calculations usually done for management and reporting reasons.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 432-440